STUDENTS’ PROBLEMS AND EXPERIENCE ON PREZI - Dzul Rachman; Iwan Setiawan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
Today technology plays an important role in pedagogy. As students, it is important for them to be equipped with various ICT presentation tools to communicate effectively and efficiently their reports and presentations. It is in this light that the objective of this study is to determine the experiences and the problems faced off the students of English department in using Prezi in the classroom. A qualitative method used in this study. The researcher took students of the fourth semester as the subject of observation because they have prior knowledge or experience use presentation tool that collaborates with pictures or videos, themes, effects, and hyperlink in order to make slides of presentation or report especially in using another presentation tool. In this study, the researcher used two instruments were observation and interview. For data collection, the researcher used focus group interview to collect information relate to their experience in implementing Prezi and observed 54 students in accessing account until sharing of Prezi. In observation period, the researcher found the students got problems in making Prezi especially feature of video, path, image, music and animation. However, they also shared some challenges in using a feature of presentation tools. For instance, they needed an internet connection to import music and video online. They also needed the Wi-Fi and/or internet connection to download Prezi.